Health Condition of Elderly People at Dhurkot Rural Municipality in Gulmi District, Nepal - Kunwar, Thaneshwar (Humanities and Social Sciences Journal, 2022)
Aging is a gradual, continuous process of natural change that begins in early adulthood. The objective of the study was to analyse the health condition of elderly people atDhurkot Rural Municipality in Gulmi district. Purposively three wards were chosen for sample population. There were 930 elderly people aged 60 years and above who had received Old Age Allowance provided by the government of Nepal. A total of 280 elderly were interviewed. Finding shows that hill Dalit elderly people have better health condition than hill Brahmin elderly people [OR=.46(.26-.81)]. Elderly people who depended on agriculture labour were found to have better health condition than elderly who depended on their own agriculture [OR=.38(.19-.81)]. Elderly belonging to the age of 65-69 years had more good health condition than that of elderly people above 75 years and above [OR= .35(.15-.79)]. Elderly people work as a household work are two times more better health condition than who do agriculture work [OR=2.13(.95-4.47)]. Elderly people living with family without spouse are better health condition than elderly live alone [OR=.22(.07-.69)]. Likewise, elderly people living with spouse and family are better health condition than elderly people living alone [OR= .33(.1-1.03)]. Various health schemes, policies and programmes can be designed in the research area and similar settings based on the study findings.